2018
DOI: 10.1038/s41598-018-25959-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially accumulated proteins involved in regulating independent and combined osmosis and cadmium stress response in Brachypodium seedling roots

Abstract: In this study, we aimed to identify differentially accumulated proteins (DAPs) involved in PEG mock osmotic stress, cadmium (Cd2+) stress, and their combined stress responses in Brachypodium distachyon seedling roots. The results showed that combined PEG and Cd2+ stresses had more significant effects on Brachypodium seedling root growth, physiological traits, and ultrastructures when compared with each individual stress. Totally, 106 DAPs were identified that are responsive to individual and combined stresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…57 Previous studies have reported that Cd exposure perturbs the membrane integrity and stimulate lipoxygenase activities, thereby catalyzing peroxidation of unsaturated fatty acids in the membranes. 16,58 Linoleic and linolenic acids are the most abundant unsaturated fatty acids in plants. Similar to BULK and ION treatments, CdS-QD exposure downregulated a few proteins involved in linoleic acid metabolism in the roots.…”
Section: Cds-qds Modulate Energy Metabolism In Soybean Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Previous studies have reported that Cd exposure perturbs the membrane integrity and stimulate lipoxygenase activities, thereby catalyzing peroxidation of unsaturated fatty acids in the membranes. 16,58 Linoleic and linolenic acids are the most abundant unsaturated fatty acids in plants. Similar to BULK and ION treatments, CdS-QD exposure downregulated a few proteins involved in linoleic acid metabolism in the roots.…”
Section: Cds-qds Modulate Energy Metabolism In Soybean Plantsmentioning
confidence: 99%
“…There is limited knowledge on the mechanisms of subcellular transport and toxicity of Cd-based QDs in plants, and the findings from Cd 2+ toxicity studies are not applicable due to unique material properties and dynamic biophysical interactions at the nanoscale. [14][15][16][17] Using gene expression analysis of Cd-tolerant mutant lines and genome-wide transcriptomics, Arabidopsis thaliana ecotypes exposed to CdS-QDs exhibited differential regulation of genes encoding antioxidant enzymes, anthocyanin production, trichoblast differentiation, root development pathways, photosynthesis, sulfur transport, metal chelation, and phenylpropanoid synthesis. 18 However, the choice of QD surface coating plays a decisive role in the process of adherence, dissolution, biological uptake and interactions at the nano-bio interface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the transcription patterns of TPX under the water-deficit and high-N treatments were highly consistent with its protein expression pattern, but poor consistency was observed between its transcription pattern and protein expression pattern under the combined treatment. The disparities between transcription levels and their corresponding protein levels have been previously reported [45,46]. It may be caused by time-space span between transcription and translation, posttranscriptional modifications, as well as differential mRNA and protein degradation rates [47] Int.…”
Section: Comparison Of Transcription and Translation Expression Levelmentioning
confidence: 86%
“…The accumulation of sodium and chloride causes plant tissue damage, thus activating oxidative stress (Baghalian et al, 2008). MDA modifies many proteins into the photosynthetic center II (PSII) to stimulate the plant to adapt to environmental stress (Chen et al, 2018). Proteins are significant focuses for radicals and two-electron oxidants in biological systems because of their plenitude and high rate constants for the response (Davies, 2016).…”
Section: Discussionmentioning
confidence: 99%